The Path of Desire: Living tantra in Northeast India - Urban, Hugh B. (Chicago and London The University of Chicago Press, 2024)
Tantra, one of the most important religious currents in South Asia, is often misrepresented as little more than ritualized sex. Through a mixture of ethnography and history, Hugh B. Urban reveals a dynamic living tradition behind the sensationalist stories. Urban shows that Tantric desire goes beyond the erotic, encompassing such quotidian experiences as childbearing and healing. He traces these holistic desires through a series of unique practices: institutional Tantra centered on gurus and esoteric rituals; public Tantra marked by performance and festival; folk Tantra focused on magic and personal well-being; and popular Tantra imagined in fiction, film, and digital media. The result is a provocative new description of Hindu Tantra that challenges us to approach religion as something always entwined with politics and culture, thoroughly entangled with ordinary needs and desires.
Keywords: Desire -- Religious aspects -- Hinduism; Folk religion -- India -- Assam; Tantrism -- India -- Assam